Spontaneous Carotid Dissection Manifested by Aphasia (Revista de Medicina Clinica, 2022)
Introduction: Carotid arterial dissection (DAC) represents the rupture of the intimate wall of the artery forming an intramural hematoma, which causes stenosis of its vascular lumen, it is associated with 45% of cerebral infarction cases in children under 45 years of age. Case Report: A 46-year-old male with an hour-long symptomatology characterized by dizziness and aphasia. The exploration without focalization data, with global aphasia, with normal vital signs, for which a diagnosis of probable cerebral infarction in evolution in the territory of the left midbrain is made, angio-magnetic resonance is performed, finding aortic dissection of left internal carotid artery. ; An intravascular procedure with stent placement was performed. With recovery ad integrum of language. Conclusion: Spontaneous carotid artery dissection requires a high index of suspicion because its symptoms can be highly variable.
Keywords: Carotid Dissection; Cerebral Infarction; Stent